2019
DOI: 10.1074/jbc.rev118.000828
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial plasticity in cell fate regulation

Abstract: Edited by John M. Denu Mitochondria are considered highly plastic organelles. This plasticity enables the mitochondria to undergo morphological and functional changes in response to cellular demands. Stem cells also need to remain functionally plastic (i.e. to have the ability to "decide" whether to remain quiescent or to undergo activation upon signaling cues to support tissue function and homeostasis). Mitochondrial plasticity is thought to enable this reshaping of stem cell functions, integrating signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 92 publications
3
91
0
1
Order By: Relevance
“…ROS (e.g., superoxide and H 2 O 2 ) are important regulators of cellular homeostasis and play an essential role in cellular stress signaling, cell survival, differentiation, proliferation, and oncogenic transformation [5,6,60]. The ETC is thought to be the main source of mitochondrial ROS in a process that can be triggered by increased respiratory rate, changes in Δψm, and dysfunctional ETC complexes.…”
Section: Discussionmentioning
confidence: 99%
“…ROS (e.g., superoxide and H 2 O 2 ) are important regulators of cellular homeostasis and play an essential role in cellular stress signaling, cell survival, differentiation, proliferation, and oncogenic transformation [5,6,60]. The ETC is thought to be the main source of mitochondrial ROS in a process that can be triggered by increased respiratory rate, changes in Δψm, and dysfunctional ETC complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have shown that mitochondrial dynamics control cell fate decisions (Bahat & Gross, 2019; Chen & Chan, 2017), including in stem cells. For example, Drp1‐induced mitochondrial fission is required for Notch‐mediated follicle cell differentiation during Drosophila oogenesis (Mitra, Rikhy, Lilly, & Lippincott‐Schwartz, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are considered multifaceted organelles that regulate stem cell fate decisions [20]. Generally, mitochondria in MSCs are maintained at a low activity level, and after MSC induction, mitochondrial DNA (mtDNA) copy number, OCR, mitochondrial biogenesis related genes (NRF1 and TFAM) expression and intracellular ATP content are enhanced [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the differentiation and homeostatic function of the adipose tissue are supported by mitochondrial biogenesis [18]. It is also worthwhile to note that BAs are rich in mitochondrial content, and the BAT has been known to play important roles in lipid metabolism and energy expenditure, with a rich expression of thermogenic markers which participate signi cantly in mitochondrial biogenesis [19,20]. Studies have demonstrated that mitochondria play an important regulatory role in determining the differentiation capacity of MSCs [17].…”
mentioning
confidence: 99%